[Fire safe cigarette briefing book] (Tufts Archival Research Center, 2007)
Briefing book on the subject of fire safe cigarettes. Claims that the objective of the book is to provide information on the history of the fire safe cigarette issue and to be a resource in the legislative battle over fire safe cigarettes. Compares the two pieces of legislation on fire safe cigarettes currently being debated. Provides statements from the senators who sponsored each bill. Contains a list of questions for both hostile and friendly witnesses to be used during a trial and a series of appendices with resources for the tobacco industry in the case of a trial.